Early Tarsorrhaphy in Conjunctival Chemosis After Orbit Bone Reconstruction. Issue 4 (June 2018) - Deng, Yuan; Li, Zhengkang
Abstract : Objective: Chemosis is a common occurrence after orbital reconstruction surgery by the transconjunctival approach. The authors propose an early tarsorrhaphy approach for treating severe conjunctival chemosis following orbital fracture repair. Methods: All severe conjunctival chemosis patients following orbital fracture repair were divided into 2 groups: tarsorrhaphy performed immediately when the eyelids could not close completely due to prominent conjunctival edema (early tarsorrhaphy, n = 10); and tarsorrhaphy performed 3 days after the appearance of severe chemosis (delayed tarsorrhaphy, n = 10). Once the conjunctiva subsided, the sutures were immediately removed. The duration of conjunctival edema was recorded. Results: The average time to resolution of severe chemosis was significantly shorter in the early versus delayed tarsorrhaphy group (3.5 ± 0.5 versus 7.2 ± 1.73 days, P  < 0.05). No recurrence of conjunctival edema occurred in any patient 4 months postoperatively. Conclusions: Early temporary tarsorrhaphy is a fast and effective method for the treatment of conjunctival chemosis following orbital fracture surgery. The sooner eyelid suturing is performed, the faster conjunctival chemosis will subside.